2022
DOI: 10.3389/fonc.2022.960056
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial intelligence to pancreatic adenocarcinoma

Abstract: Background and ObjectivesPancreatic cancer (PC) is one of the deadliest cancers worldwide although substantial advancement has been made in its comprehensive treatment. The development of artificial intelligence (AI) technology has allowed its clinical applications to expand remarkably in recent years. Diverse methods and algorithms are employed by AI to extrapolate new data from clinical records to aid in the treatment of PC. In this review, we will summarize AI’s use in several aspects of PC diagnosis and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 122 publications
0
6
0
1
Order By: Relevance
“…They focused on the analysis of endoscopic ultrasound images, CT images, and magnetic resonance images using AI algorithms. Chen et al [ 47 ] provided a literature review on the application of AI for pancreatic cancer. They included articles from PubMed and Google Scholar by using the keywords AI and pancreatic cancer and focused on risk assessment, treatment, diagnosis, and prognosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They focused on the analysis of endoscopic ultrasound images, CT images, and magnetic resonance images using AI algorithms. Chen et al [ 47 ] provided a literature review on the application of AI for pancreatic cancer. They included articles from PubMed and Google Scholar by using the keywords AI and pancreatic cancer and focused on risk assessment, treatment, diagnosis, and prognosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They included articles from PubMed and Google Scholar by using the keywords AI and pancreatic cancer and focused on risk assessment, treatment, diagnosis, and prognosis of pancreatic cancer. They did not follow the PRISMA guidelines to ensure the reliability and transparency of the work [ 47 ]. Moreover, Dumitrescu et al [ 10 ] conducted a systematic review by following PRISMA guidelines and focused on the diagnostic value of AI-based ultrasound for the diagnosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research highlights that the significant risk factors for pancreatic cancer include age, gender, race, a family history of inheritance, smoking, drinking, obesity, chronic pancreatitis, hepatitis, and persons living with human immunodeficiency virus (PLWH) 4–6 . Additionally, patients with diabetes mellitus (DM) have an elevated risk for pancreatic cancer 6–9 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Additionally, patients with diabetes mellitus (DM) have an elevated risk for pancreatic cancer. [6][7][8][9] Regarding the correlation between diabetes and pancreatic cancer, previous publications observed that up to 85% of pancreatic cancer patients have diabetes at the time of the cancer diagnosis. 10 The increased risk of pancreatic cancer is two to three times higher for patients with diabetes than patients without diabetes.…”
Section: Introductionmentioning
confidence: 99%